2011
DOI: 10.1530/rep-10-0536
|View full text |Cite
|
Sign up to set email alerts
|

Key gene regulatory sequences with distinctive ontological signatures associate with differentially endonuclease-accessible mouse sperm chromatin

Abstract: Using a well-established endonuclease-based chromatin dissection procedure in conjunction with both experimental comparative genome hybridisation (CGH) array profiling and in silico data mining, we show that mouse spermatozoa contain chromatin that is sensitive and resistant to digestion with micrococcal nuclease (MNase). Sequences represented in the micrococcal nuclease digestion solubilised (MNDS) but not the MND insoluble (MNDI) chromatin are strongly enriched in chromosomal regions of high gene density. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Two studies isolated solubilized mononucleosome-sized fragments after MNase digestion of human sperm, finding enrichment over the promoters of key developmental regulators, with a very strong correlation with GC content (Brykczynska et al, 2010; Hammoud et al, 2009; Vavouri and Lehner, 2011). Somewhat different results were obtained via tiling microarray analysis of DNA released after light restriction enzyme or MNase digestion of human and mouse sperm, with gene and promoter-rich regions flanked by CTCF sites very broadly overrepresented in much longer (Megabase-scale) domains (Arpanahi et al, 2009; Saida et al, 2011). …”
Section: Discussionmentioning
confidence: 92%
“…Two studies isolated solubilized mononucleosome-sized fragments after MNase digestion of human sperm, finding enrichment over the promoters of key developmental regulators, with a very strong correlation with GC content (Brykczynska et al, 2010; Hammoud et al, 2009; Vavouri and Lehner, 2011). Somewhat different results were obtained via tiling microarray analysis of DNA released after light restriction enzyme or MNase digestion of human and mouse sperm, with gene and promoter-rich regions flanked by CTCF sites very broadly overrepresented in much longer (Megabase-scale) domains (Arpanahi et al, 2009; Saida et al, 2011). …”
Section: Discussionmentioning
confidence: 92%
“…CTCF-binding sites are highly enriched in MNase-sensitive sperm DNA fractions in both, humans [4] and mice [31]. Future studies addressing how the sites of histone retention in sperm are determined are clearly required.…”
Section: Discussionmentioning
confidence: 99%
“…Work conducted in this and other laboratories suggests that the DNA in human and mouse sperm is carefully and systematically organised in the nucleus into distinct geographical domains ( Figure 1). [30][31][32] These studies showed that some domains are enriched in histones, 33 which can account for their hitherto unexplained persistence in sperm nuclei alongside the more abundant protamines. 34,35 Histone-bound sperm chromatin domains are enriched in developmental gene sequences expressed in early embryogenesis.…”
Section: Summary Of Evidence Leading Up To and Justification For The mentioning
confidence: 97%
“…34,35 Histone-bound sperm chromatin domains are enriched in developmental gene sequences expressed in early embryogenesis. 30,32,33 We hypothesised that damage to these domains was critically relevant for subsequent early embryonic development and could account for the early pregnancy failure observed after both IVF and ICSI-based procedures. 36 Failure of the embryo to thrive following successful implantation may be related to the fragmented or deranged paternal DNA resulting in sequences that are important for early embryological function remaining bound to histones.…”
Section: Summary Of Evidence Leading Up To and Justification For The mentioning
confidence: 99%